United Kingdom-Anguilla-British Overseas Territory : Technical Assistance Report-Report on External Sector Statistics Mission (March 27-31, 2017). (IMF Staff Country Reports; Country Report ;, 2018)
A technical assistance (TA) mission on external sector statistics (ESS) was conducted in The Valley, Anguilla, during March 27-31, 2017. This was the first mission to Anguilla carried out as part of the Caribbean Regional Technical Assistance Centre (CARTAC) work program on external sector statistics (ESS) and in response to requests from the Anguilla Statistics Department (ASD) of Anguilla's Ministry of Finance, Economic Development, Commerce, Tourism, Land and Physical Planning (MFED).1 The purpose of the mission was to assist the ASD in strengthening the compilation and dissemination of ESS. This is intended to facilitate a robust assessment of external sector developments and policy impact. Reliable ESS are essential for informed economic policy-making by the authorities.